The preservation role of maritime natural and cultural heritage in Batu Bedil Geosite the Belitong Global Geopark area through a sustainable eco-culture tourism approach - Dadang Hikmah Purnama; Aryandini Novita; Roby Ardiwidjaja; Nurul Laili; Endang Widyastuti (Heritage and Sustainable Development)
This article aims to provide a model for developing tourist destinations in the Batu Bedil Geosite, Belitong, Indonesia, by evaluating previous studies. Researchers use the evaluation results as a reference to develop eco-culture tourism in the Batu Bedil Geosite, focusing on cultural heritage and the surrounding natural environment. This research is a literature study, which involves the collection and analysis of data sources and information relevant to the research theme. Based on previous research, the management of the Belitong Global Geopark since its establishment has only focused on geodiversity and biodiversity. The Belitong Global Geopark has not fully integrated the contribution of cultural heritage to its development. Using cultural heritage in geopark areas provides a unique perspective on how communities adapt to their environment - a process in which audiences, as researchers, policymakers, and stakeholders, must put cultural aspects on par with economic and environmental considerations.